2020
DOI: 10.1007/s00401-020-02181-3
|View full text |Cite|
|
Sign up to set email alerts
|

Large-scale pathway specific polygenic risk and transcriptomic community network analysis identifies novel functional pathways in Parkinson disease

Abstract: Polygenic inheritance plays a central role in Parkinson disease (PD). A priority in elucidating PD etiology lies in defining the biological basis of genetic risk. Unraveling how risk leads to disruption will yield disease-modifying therapeutic targets that may be effective. Here, we utilized a high-throughput and hypothesis-free approach to determine biological processes underlying PD using the largest currently available cohorts of genetic and gene expression data from International Parkinson’s Disease Geneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 35 publications
6
104
0
Order By: Relevance
“…The MSigDB was used to extract gene sets representative of biological pathways, and a pathway-specific polygenic effect score was constructed for each dataset. In support of the previous pathway-specific analyses [ 36 , 37 ], the study found a significant association between PD risk and the endocytic membrane trafficking and mitochondrial function pathways [ 38 ]. Most notably, this approach identified significant associations between risk of PD and novel biological pathways.…”
Section: Utilizing Genetic Risk Profiling To Identify Biological Psupporting
confidence: 85%
See 2 more Smart Citations
“…The MSigDB was used to extract gene sets representative of biological pathways, and a pathway-specific polygenic effect score was constructed for each dataset. In support of the previous pathway-specific analyses [ 36 , 37 ], the study found a significant association between PD risk and the endocytic membrane trafficking and mitochondrial function pathways [ 38 ]. Most notably, this approach identified significant associations between risk of PD and novel biological pathways.…”
Section: Utilizing Genetic Risk Profiling To Identify Biological Psupporting
confidence: 85%
“…Overall, the study concluded that the main contributors to PD etiology are molecular processes underlying protein misfolding and aggregation, post-translational protein modification, immune response, membrane and intracellular trafficking, lipid metabolism, synaptic transmission, endosomal–lysosomal dysfunction and apoptosis mediated by initiator and executioner caspases ( Figure 2 ). This was the first study to test the contribution of thousands of molecular processes to PD risk in an unbiased and data-driven manner and provide a foundational resource for the PD community through a publicly available pathways browser [ 38 ] ( ).…”
Section: Utilizing Genetic Risk Profiling To Identify Biological Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Several PD risk genes implicated by Genome-Wide Association Studies (GWAS) also have roles at the synapse including (but not limited to) SH3GL2, SYNJ1, RIMS1, VAMP4, SYT4, ANK2, LRRK2, SNCA, STX1B, SYT11, and VPS35 (Nalls et al, 2014(Nalls et al, , 2019Chang et al, 2017;Blauwendraat et al, 2020;Grenn et al, 2020). GWAS and subsequent analyses of gene-phenotypic trait associations (Heilbron et al, 2019) and cell-type-specific expression patterns discovered an enrichment of risk-associated genes in neurons (Bandres-Ciga et al, 2020;Bryois et al, 2020), as well as oligodendrocytes, astrocytes, and endothelium (Reynolds et al, 2019;Bryois et al, 2020). While cell-type-specific variant-associated changes in gene expression remain unexplored due to the technical challenge of performing single-cell transcriptomics and whole-genome sequencing in the human brain, associations between risk variants and gene expression at the tissue level have been found using quantitative trait loci (QTL) mapping (Nica et al, 2010;Hernandez et al, 2012;Westra and Franke, 2014;Guelfi et al, 2020).…”
Section: Role Of Risk Genes In Synaptic Defects In Pdmentioning
confidence: 99%
“…ATG14 function is required for both basal and inducible autophagy but also determines the localization of the autophagy-specific PI3-kinase complex and contributes to autophagosome formation 25 . Interestingly, there is genetic, pathological, and experimental evidence suggesting an important role for autophagy impairment in PD 26,27 .…”
Section: Discussionmentioning
confidence: 99%